Sistem E-Presensi Berbasis Web Dengan Kode QR di SMK Negeri 2 Cimahi - Dewi Rosmala; Muhammad Ichwan; Dicky Darmawan; Fadillah Muamar Fauzan; Agil Yudistira; Mochamad Hafied Ibni Anwar (Lembaga Pengembangan Kinerja Dosen, 2024)
The web-based e-Attendance system with QR Code at SMK Negeri 2 Cimahi enhances student attendance monitoring digitally. By integrating QR Code technology, students easily record their attendance by scanning a QR Code on the attendance page. The system’s key advantage is automatic attendance recording, providing real-time access for teachers and administrative staff. The user-friendly interface ensures accurate monitoring and efficient data management, minimizing errors and offering a precise understanding of student attendance. The implementation of QR Code technology has improved administrative efficiency and reduced errors, leading to better insights into student attendance. Data analysis enables teachers to take appropriate actions to enhance student engagement, fostering a more responsive learning environment. Overall, the e-Attendance system significantly optimizes student attendance management in the digital era.